2022
DOI: 10.1088/1755-1315/1012/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Test of Newness Uniformity and Uniqueity 11 Polinela Hybrid Corn Lines

Abstract: Apart from being a staple food, corn has become more important because it is a staple for the animal feed industry. The need for seeds from year to year continues to increase. Eleven promising hybrid maize lines as candidates for new high yielding varieties assembled by Polinela need further testing, including the NUSU test (new, unique, stable, and uniform). The research objective was to test the novelty, uniqueness, uniformity, and stability of the 11 new hybrid maize lines. The treatments were 11 hybrid mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The narrow variability value indicates that all the characters tested in the F8 generation have had high uniformity. [15] stated that uniformity testing is determined by the magnitude of the variation that occurs in a population, the smaller the variation, the higher the uniformity and conversely. [16] stated that homogeneity in the observations made showed that the population has been uniform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow variability value indicates that all the characters tested in the F8 generation have had high uniformity. [15] stated that uniformity testing is determined by the magnitude of the variation that occurs in a population, the smaller the variation, the higher the uniformity and conversely. [16] stated that homogeneity in the observations made showed that the population has been uniform.…”
Section: Methodsmentioning
confidence: 99%
“…Generation F8 is the 7th generation of segregation, the homozygous percentage is 99.21%. [15] stated that a plant is considered uniform if the properties possessed remain the same even though it is planted in different environments. [19] stated that genotypes with a uniform character mean that selection activities in these characters no longer need to be selected, because the phenotype of these characters is already consistent.…”
Section: Methodsmentioning
confidence: 99%
“…Pest control was carried out using emamectin benzoate at 100 g ha -1. The observed traits (Jahangirlou et al, 2021;Kartahadimaja & Syuriani, 2021) are presented in Table 1.…”
Section: Traits Observationmentioning
confidence: 99%